MIDAS: A Miniature Device for Real‐Time Determination of the Identity and Energy of Particles in Space. Issue 3 (19th March 2020) - Lambropoulos, C. P.; Potiriadis, C.; Theodoratos, G.; Kazas, I.; Papadimitropoulos, C.; Loukas, D.; Glikiotis, I.; Karafasoulis, K.; Paschalis, P.; Kοkavesis, M.; Dimopoulos, S.; Delakoura, A.; et al.
Abstract: The Miniaturized Detector for Application in Space (MIDAS) device is developed in response to the requirement of the European Space Agency for a device whose size, power consumption, and radiation data output would increase the level of space‐flight crew autonomy regarding operational decisions related to radiation hazards. It is designed as a wristwatch‐dimension cube detector for measuring track direction and energy deposition in silicon pixels, as well as energy depositions by neutrons in a plastic scintillator, which is the core of the cube. Miniaturization was achieved by using fully depleted silicon pixel detectors with the signal processing electronics residing on pixel. The device concept, simulated performance, and first measurements are presented. Simulation results indicate that it is possible to discriminate all significant ions with the aid of appropriate variables constructed using the data provided by the device. 252 Cf energy spectra were reconstructed successfully using measurements obtained with the first device prototype. Key Points: The first design of depleted monolithic active pixel sensors for charged particle measurement in space is presented A sensitive cube with wristwatch dimensions for dosimetry of charged particles and neutrons in mixed radiation fields has been designed